Program Studi Ners Spesialis Keperawatan Jiwa Fakultas Ilmu Keperawatan Universitas Indonesia, Kampus UI Depok, Jakarta10430, Indonesia - Riris Ocktryna Silitonga; Achir Yani S. Hamid; Yossie Susanti Eka Putri (Jurnal Keperawatan Jiwa (JKJ): Persatuan Perawat Nasional Indonesia, 2014)
People with tendency to act aggressively shown that they used destructive coping strategies to express their anger. Aim of this paper was to describe the application of Model Adaptasi Roy and Johnson’s Behavioural System Model, focusing on aggresive behavior. Assertive training intervention that provided to 15 clients and cognitive behaviour therapy were that provided to 24 clients. Result of this study shown that sign and symptoms of aggressive behaviour were decreased and increased of client's ability to express their emotion in contructive way. Recommended the Model Adaptasi Roy and Johnson’s Behavioural System Model with assertive training and cognitive behaviour therapy were to derecrease aggresive behaviour.